2018
DOI: 10.15294/jpii.v7i4.14437
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Versus Printed Book: Comparison Study on the Effectivity of Senior High School Physics Book

Abstract: This study aimed to examine the effectiveness of senior high school physics book both interactive electronic and printed, viewed from the difference in gender and material characteristics. The research used Quasi-Experimental Design with Non-Equivalent posttest-pretest control group design. The data were collected through physics tests from six senior high schools in Lampung Province, Indonesia and analyzed on ANOVA and multiple comparisons to determine the differences in learning outcomes (affectivity) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…Meanwhile, research from (Rasmawan, 2020;Supriyadi et al, 2020) takes a specific theme again, but the study material is not economic learning, especially macroeconomics. Then several previous studies from several experts showed that the effectiveness of digital books can be compared with ordinary printed books (Uygarer & Uzunboylu, 2017;Suyatna et al, 2018;Abed, 2019). Then in terms of the sample used, the study was limited to using only one class of 36 samples, this is different from previous research from (Shehu & Jere, 2016;Ibrahim & Alqahtani, 2018) which took more samples than the author's research.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Meanwhile, research from (Rasmawan, 2020;Supriyadi et al, 2020) takes a specific theme again, but the study material is not economic learning, especially macroeconomics. Then several previous studies from several experts showed that the effectiveness of digital books can be compared with ordinary printed books (Uygarer & Uzunboylu, 2017;Suyatna et al, 2018;Abed, 2019). Then in terms of the sample used, the study was limited to using only one class of 36 samples, this is different from previous research from (Shehu & Jere, 2016;Ibrahim & Alqahtani, 2018) which took more samples than the author's research.…”
Section: Resultsmentioning
confidence: 96%
“…Previous research from several experts (Dewi et al, 2018;Liao et al, 2018;Wusqo et al, 2021) chose non-economic materials in developing a digital book. Then in terms of research variables, several experts examined the effectiveness of using digital books with printed books (Suyatna et al, 2018;Siwiendrayanti et al, 2019;Suryani et al, 2021). Previous research shows that there is no research on the development of digital books on macroeconomic material, previous research is only limited to the development of macroeconomic modules.…”
Section: Introductionmentioning
confidence: 99%
“…(Ayvaz-tuncel & Tuncel, 2019;Chaaban et al, 2021;Osadebe & Osadebe, 2020). In the learning process, gender can be an influential factor (Fitriani et al, 2019;Suyatna et al, 2018). Females have a clearer way of thinking with more organized emotions than males (Xu & Waniganayake, 2018).…”
Section: Perception Of Female and Male Students In Class B On Mathematical Physics E-modulementioning
confidence: 99%
“…A person's perception can be influenced by gender, which affects differences in roles, functions, positions, responsibilities and behavioral rights of a person which are broadly related to one another (Dharma, 2016). Gender can be a factor that influences the learning process and the achievement of learning outcomes (Liu & Young, 2017;Bhagat & Chang, 2018;Chiu, 2018;Suyatna et al, 2018;Fitriani et al, 2019). Based on gender, it can be seen that there is a positive perception that shows that e-modules can help students understand mathematics and physics material for males and females.…”
Section: Introductionmentioning
confidence: 99%
“…Gender men and women have different levels of perception. Gender is a factor that also needs to be considered in education (Darmaji, Astalini, Kurniawan & Aldila, 2022;Fitriani, Asy'ari, Zubaidah & Mahanal, 2019;Suyatna, Maulina, Rakhmawati & Khasanah, 2018). For example, Gender women are generally superior and skilled in various activities (Beddoes, 2018;Saleh & Mazlan, 2019;Rizal, Rusdiana, Setiawan & Siahaan, 2020).…”
Section: Introductionmentioning
confidence: 99%